Vehicle refuelling, use of domestic wood heaters and the risk of childhood brain tumours: Results from an Australian case–control study. Issue 2 (4th October 2014) - Greenop, Kathryn R.; Hinwood, Andrea L.; Fritschi, Lin; Scott, Rodney J.; Attia, John; Ashton, Lesley J.; Heath, John A.; Armstrong, Bruce K.; Milne, Elizabeth
<x xml:space="preserve">Abstract</x> Background The aetiology of childhood brain tumours (CBT) is largely unknown. Damage to germ cells after parental exposure to airborne carcinogens, such as volatile organic compounds and polycyclic aromatic hydrocarbons is one plausible pathway. This analysis aimed to investigate whether parental refuelling of vehicles or the use of domestic wood heaters in key time periods relating to the child's birth was associated with an increased risk of CBT. Procedure Cases <15 years of age were recruited through 10 paediatric oncology centres around Australia; controls were recruited through nationwide random‐digit dialling, frequency matched to cases on age, sex and State of residence. Exposure to refuelling and wood heaters was ascertained through questionnaires from both parents. Odds ratios (ORs) and confidence intervals (CIs) were estimated using unconditional logistic regression, adjusting for relevant covariates. Results Data were available for 306 case and 950 control families. Paternal refuelling ≥4 times/month was associated with an increased risk of CBT (OR 1.59, 95% CI: 1.11, 2.29), and a dose‐dependent trend was observed (P = 0.004). No association was seen for maternal refuelling. Use of closed, but not open, wood heaters before (OR 1.51, 95% CI: 1.05, 2.15) and after (OR 1.44, 95% CI: 1.03, 2.01) the child's birth was associated with increased risk of CBT, but dose‐response relationships were weak or absent. Conclusions Paternal refuelling of vehicles ≥4 times/month and the use of closed wood heaters before the child's birth may increase the risk of CBT. Replication in larger studies is needed. Pediatr Blood Cancer 2015;62:229–234. © 2014 Wiley Periodicals, Inc.